Identification of risk factor in oil and gas projects in South Africa - Sadiki, Ndavheleseni (Department of Construction Economics and Management, 2025)
Background: South African oil and gas projects face several risks, which, if not adequately managed, could lead to project failures and consequently halt upstream oil and gas activities in the country. Therefore, identifying the risk factors is critical for effective risk control, transfer, or management. Purpose: The research aims to identify risk factors affecting oil and gas projects in South Africa. It further examines the identified risks to establish if they change as the project moves from the exploration to the development phase and establish whether the risks in the literature apply to South Africa. In addition, the research seeks to identify tools used to identify risk factors in South African oil and gas projects. Methodology: The study adopted a qualitative methodology to identify the risk factors. The snowball sampling technique was adopted to recruit the participants. Data was collected from participants via an online self-administration survey until a saturation point was reached. The respondents were 26 diverse, experienced professionals from government agencies, oil and gas/energy companies, funding institutions, and consultants/contractors in the South African oil and gas sector. Findings: The identified risk factors include regulatory uncertainty, a slow regulatory process, stringent NEMA financial provisioning regulations, public objections, challenging economic factors, geological/subsurface uncertainties geological/subsurface uncertainties, Inclined offshore weather and a lack of experienced human resource skills and local contractors. Data analysis revealed that the identified list of risk factors does not materially change as the projects move from one exploration phase to the development phase. Despite the remote location of South Africa from the regions with active oil and gas activities, the findings showed that the identified factors were not entirely unique to South Africa. The data further revealed that various tools are used to identify risk factors, but brainstorming was popular with most participants. Value of study: The output from the study contributes to knowledge and lays the foundation for future exploration, evaluation and management of risk in South African upstream oil and gas projects. It also provides insights to stakeholders involved in the sector.